Early hypothermia as risk factor in severely burned patients: a retrospective outcome study - Ziegler, Benjamin; Kenngott, Theresa; Fischer, Sebastian; Hundeshagen, Gabriel; Hartmann, Bernd; Horter, Johannes; Münzberg, Matthias; Kneser, Ulrich; Hirche, Christoph (Burns, 2019)
Introduction - Burn trauma-related hypothermia is a frequent observation but risk factors and impact on patient related outcome are ambiguously reported. It is expected that hypothermia is associated with increased mortality and reduced overall outcome in severely burned patients, but available evidence is limited. - Methods - This retrospective single-center-study reviewed preclinical service protocols and medical records of patients sustaining a burn with a total body surface area (TBSA) ≥15% from 2008 to 2012. General patient and burn specific characteristics, outcome parameters as well as body temperature at admission measured via urine catheter or nasal temperature probe were recorded and statistically analyzed comparing normothermic (≥36 °C), mild hypothermic (<36 °C) and severely hypothermic (<34.5 °C) patients. Chi-square test was performed to demonstrate impact of hypothermia on primary outcome parameters and to reveal risk factors for developing hypothermia. To assess independent influences on mortality, a multivariate logistic regression analysis was performed. - Results - Out of 300 patients matching inclusion criteria, a sufficient record of temperature was found in 144 patients (48%). Out of 141 eligible patients with an average burn extent (SD) of 33.38% (24.5%) TBSA, 31.9% (n = 45) suffered from severe hypothermia (<34.5 °C) and 28.4% (n = 40) showed mild hypothermia. Total burn extent, presence of full thickness burns, presence of inhalation injury, preclinical mechanical ventilation and administration of sedative drugs were risk factors for developing hypothermia. Patients’ age, total burn extent and presence of full thickness burns could be identified as independent factor for mortality. Although a trend towards an independent positive influence of normothermia at admission on mortality was seen, it was not statistically significant. - Conclusion - Incidental hypothermia of burned patients is associated with an increased mortality and needs to be addressed by emergency health care providers and immediately at the burn center. Especially patients with extensive burns, full-thickness burns, inhalation injury or patients undergoing preclinical intubation are at risk for hypothermia and benefit from any measures for temperature preserving.